2019
DOI: 10.1016/j.bpj.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Control of Frequency Modulation of cAMP Oscillations due to Calcium in Dendritic Spines

Abstract: The spatiotemporal regulation of cyclic adenosine monophosphate (cAMP) and its dynamic interactions with other second messengers such as calcium are critical features of signaling specificity required for neuronal development and connectivity. cAMP is known to contribute to long-term potentiation and memory formation by controlling the formation and regulation of dendritic spines. Despite the recent advances in biosensing techniques for monitoring spatiotemporal cAMP dynamics, the underlying molecular mechanis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 108 publications
(158 reference statements)
0
29
0
Order By: Relevance
“…We also note that compared to the Ca 2+ dynamics in the ER and the MERC, the mitochondrial Ca 2+ and ATP dynamics are smoother, indicating that the mitochondria retain the lower frequency information and not the higher frequency (Supplemental Fig. 2 b, c) 54 , 55 . MERC calcium is not affected by the diffusion coefficient of calcium (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 81%
“…We also note that compared to the Ca 2+ dynamics in the ER and the MERC, the mitochondrial Ca 2+ and ATP dynamics are smoother, indicating that the mitochondria retain the lower frequency information and not the higher frequency (Supplemental Fig. 2 b, c) 54 , 55 . MERC calcium is not affected by the diffusion coefficient of calcium (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 81%
“…• In response to a glutamate release event coupled with a voltage stimulus (primarily, an excitatory postsynaptic potential (EPSP) and a backpropagating action potential (BPAP)), N-methyl-D-aspartate receptors (NMDAR) and voltage sensitive calcium channels (VSCC) open on the spine membrane, resulting in an influx of Ca 2+ into the spine. Calcium influx into the spine is the first step in numerous different signaling pathways important for synaptic function and from a modeling perspective is one of the most studied event in spines [10][11][12][13][14][15][16]. This voltage depolarization and subsequent calcium influx occurs over the millisecond timescale and is the fastest timescale considered in our model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fluorescence experiments have shown that the dendritic spine necks act as a diffusion barrier to calcium ions, preventing ions from entering the dendritic shaft [112]. Complementary to this and other experiments, various physical models solving reaction-diffusion equations in idealized geometries have been developed to further interrogate the structure-function relationships [51,100,111,[117][118][119].…”
Section: Discussionmentioning
confidence: 99%
“…In a simulated model, the confinement of molecules can be presented as boundary conditions on a marked mesh region ( Fig 1D). Depending on the situation, such localizations can be arbitrarily or randomly assigned for hypothesis testing [51] Alternatively, the regions of confinement may be informed by the electron micrographs themselves or correlated from another experimental approaches. A robust mesh generation tool capable of handing and resolving problems across all workflow steps including boundary marking and other metadata curation is necessary to support simulations from images of subcellular scenes (Fig 1E).…”
Section: Plos Computational Biologymentioning
confidence: 99%